Tolerance to the Antinociceptive Effect of Morphine in the Absence of Short-Term Presynaptic Desensitization in Rat Periaqueductal Gray Neurons - Fyfe, Leon W. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Opioids activate the descending antinociceptive pathway from the ventrolateral periaqueductal gray (vlPAG) by both pre- and postsynaptic inhibition of tonically active GABAergic neurons (i.e., disinhibition). Previous research has shown that short-term desensitization of postsynaptic μ-opioid receptors (MOPrs) in the vlPAG is increased with the development of opioid tolerance. Given that pre- and postsynaptic MOPrs are coupled to different signaling mechanisms, the present study tested the hypothesis that short-term desensitization of presynaptic MOPrs also contributes to opioid tolerance. Twice-daily injections of morphine (5 mg/kg s.c.) for 2 days caused a rightward shift in the morphine dose-response curve on the hot plate test (D(50) = 9.9 mg/kg) compared with saline-pretreated (5.3 mg/kg) male Sprague-Dawley rats. In vitro whole-cell patch-clamp recordings from vlPAG slices revealed that inhibition of evoked inhibitory postsynaptic currents (eIPSCs) by the MOPr-selective agonist [d-Ala(2),N-Me-Phe(4),Gly(5)-ol]-enkephalin was decreased in morphine-tolerant (EC(50) = 708 nM) compared with saline-pretreated rats (EC(50) = 163 nM). However, short-term desensitization of MOPr inhibition of eIPSCs was not observed in either saline- or morphine-pretreated rats. Reducing the number of available MOPrs with the irreversible opioid receptor antagonist, β-chlornaltrexamine decreased maximal MOPr inhibition with no evidence of desensitization, indicating that the lack of observed desensitization is not caused by receptor reserve. These results demonstrate that tolerance to the antinociceptive effect of morphine is associated with a decrease in presynaptic MOPr sensitivity or coupling to effectors, but this change is independent of short-term MOPr desensitization.